ORBIT REDUCTION IN INSAR FOR DEFORMATION OBSERVATIONS MOUNT MERAPI - Agustan, Agustan (Departemen Teknik Geomatika ITS, 2016)
Ground deformation is an important parameter to monitor volcanic activities. It reflects the dynamic processes beneath the surface and should be monitored to understand the volcano status. One technique to monitor ground deformation is Interferometric Synthetic Aperture Radar (InSAR) which works based on radar data that observed whether by airplane or satellite. One important factor in InSAR data processing is orbital effect that appears as a systematic phase in interferogram. The systematic orbital phase can be modelled by mathematical approach especially polynomial equation. This article assesses the utilization of polynomial approach to reduce the orbital phase by using free open source software. As a case study, ALOS-PALSAR data for Merapi Volcano is chosen and it is found that the polynomial function order 2 to 4 is suitable to reduce orbital phase for InSAR estimates after phase unwrapping process.